2011
DOI: 10.1021/nn2007089
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring of the Growth, Intermediate Phase Transformations and Templating of Single Crystal VO2 Nanowires and Nanoplatelets

Abstract: Direct in situ optical and photoelectron emission microscopy observations of the nucleation and growth of VO(2) meso- and nanostructures using thermal transport of V(2)O(5) precursor in a vacuum or in an inert-gas environment were conducted. During nanostructure reductive growth, the formation, coexistence, and transformation of the intermediate oxide phases and morphologies were observed and characterized structurally and compositionally. The composition, structure, and morphology of the resultant nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 46 publications
5
80
0
Order By: Relevance
“…11,[65][66][67] Consequently it is of great importance to develop efficient methods to prepare such nanoparticles in large quantities and over extended surfaces. In fact, there have been numerous prior studies on VO 2 -based nanoparticles, and recent investigations have been conducted with hydrothermal/solvothermal/colloidal techniques, 27,49,50,64, vapor transport, 56,[109][110][111][112][113][114][115] anodization, 116 polymer-assisted deposition, 117,118 and templating. 29,119 References to earlier studies on the manufacturing of nanostructured VO 2 -based materials can be found elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…11,[65][66][67] Consequently it is of great importance to develop efficient methods to prepare such nanoparticles in large quantities and over extended surfaces. In fact, there have been numerous prior studies on VO 2 -based nanoparticles, and recent investigations have been conducted with hydrothermal/solvothermal/colloidal techniques, 27,49,50,64, vapor transport, 56,[109][110][111][112][113][114][115] anodization, 116 polymer-assisted deposition, 117,118 and templating. 29,119 References to earlier studies on the manufacturing of nanostructured VO 2 -based materials can be found elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable effort have in recent years been expended to the control of the growth of VO 2 NWs using simple thermal evaporation methods14151617. Usually, VO 2 NWs are preferentially grown on substrates such as silicon, oxidized silicon surface, fused quartz, etc., through a vapor-solid (VS) process17.…”
mentioning
confidence: 99%
“…Other methods that have been explored include: 1) directed and heteroepitaxial growth of VO 2 NWs on special substrates with a certain lattice match of surfaces such as a-cut/c-cut sapphire, c-cut GaN, (110) TiO 2 etc. 1518 2) several alternative templating techniques for the control of the position and orientation of VO 2 nanostructures including: (a) surface patterning with precursor powder16 and (b) templating against a microstructure substrate15. However, the efforts that have been expended in this direction suffer from drawbacks such as expensive epitaxial substrates as mentioned above and/or a poor product density.…”
mentioning
confidence: 99%
“…In reducing atmosphere thermal decomposition at 700°C (2 V 2 O 5 ! 4VO 2 þ O 2 ) results in nucleation of thermally stable VO 2 nanocrystals with a high melting point of 1970°C [22]. As aforementioned, the nanowires grow preferentially in c R crystal axis direction by vapor transport of VO 2 close to the substrate edge in form of free standing single-clamped VO 2 nanowires with sub-lm diameters between of 120 up to 370 nm and lengths in the range of 30-70 lm.…”
Section: Methodsmentioning
confidence: 90%